PERSEPSI PERAN GENDER TERHADAP PEKERJAAN DOMESTIK DAN PUBLIK PADA MAHASISWA IPB - Herien Puspitawati (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
One of the purposes of the Millenium Development Goals (MDGs) is to pursue the gender equality and womenempowerment to eradicate the gender gap. In general, there has been existed partnership between men and women in daily living. Theaims of the study were to analyze: (1) The characteristics of the undergraduate students, (2) The characteristics of the students’ family(parents’ education, parents’ occupation, and family income), and (3) the perception of students toward gender roles in domestic and publicsocialactivities. Results pointed out that women are viewed by community as actors who have roles in expresssive figures and havefunctions as care taker and educator of the family, while men are viewed by community as actors who have roles in instrumental figures andhave functions as main breadwinner. Women have more gender perspective than men. It means that women have thought in more flexibleways that gender roles could be changed and exchanged between men and women. Based on the Spearmen correlation test, it showed thatthe more individual has gender perspectives in domestic gender roles, the more that individual has gender perspectives in public and socialroles, and vice versa. Finally, there was indication that the higher the social status of the father, then the more perception of the father towardpublic and social roles that tended to be part of the men’s roles rather than women’s roles, as patriarchy system placed men to be mainbreadwinners.